REDUCTION OF GROUNDWATER IN â€œINTERFACEâ€ COASTAL AREA - arrina, (ReTII, 2020)
Research on seawater interfaces or intrusion has been carried out in various fields, so in this paper, review literature is carried out to gather information about this to determine the subsidence of groundwater levels and chemical analysis of groundwater, and the Modflow. This research uses quantitative methods. The hydrogeological problem in the coastal area is an important thing to discuss because the coast generally has the characteristics and availability of abundant freshwater but it is difficult to get water, this is due to inadequate quality, in other areas freshwater sources are also difficult to find. Seawater intrusion is the difference in height between seawater and freshwater. If the groundwater level is lower than the sea level, seawater intrusion can occur. To find out that in an area affected by seawater intrusion, a chemical analysis of groundwater or chloride ion analysis is necessary, which requires water sampling after which laboratory tests are carried out. Meanwhile, MODFLOW is used as a pattern of groundwater distribution and groundwater potential, groundwater velocity.